Photoheat-induced Schottky nanojunction and indirect Mott transition in VO2: photocurrent analysis. (1st February 2016) - Kim, Hyun-Tak; Kim, Minjung; Sohn, Ahrum; Slusar, Tetiana; Seo, Giwan; Cheong, Hyeonsik; Kim, Dong-Wook
Abstract: In order to elucidate a mechanism of the insulator-to-metal transition (IMT) for a Mott insulator VO2 (3 d 1 ), we present Schottky nanojunctions and the structural phase transition (SPT) by simultaneous nanolevel measurements of photocurrent and Raman scattering in microlevel devices. The Schottky nanojunction with the monoclinic metallic phase between the monoclinic insulating phases is formed by the photoheat-induced IMT not accompanied with the SPT. The temperature dependence of the Schottky junction reveals that the Mott insulator has an electronic structure of an indirect subband between the main Hubbard d bands. The IMT as reverse process of the Mott transition occurs by temperature-induced excitation of bound charges in the indirect semiconductor band, most likely formed by impurities such as oxygen deficiency. The metal band (3 d 1 ) for the Mott insulator is screened (trapped) by the indirect band (impurities).